Analiss Rasio Profitabilitas Untuk Menilai Kinerja Keuangan Pada PT. Timah Tbk Tahun 2019-2022 - Aula Mustaghfiroh; Sintaliya Sintaliya; Adelina Citradewi (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
In other words, the profitability ratio may be used to gauge both the performance of the firm as well as its capacity to make productive use of its assets. It demonstrates the organization's capacity to earn profits. When a firm's profitability ratio is high, the total amount of profit that the company has accumulated is also high. How the calculation results of Gross Profit Margin, Net Profit Margin, Return on Assets, and Return on Equity at PT. Timah Tbk, how is the growth of financial performance at PT. Timah Tbk in terms of profitability ratios from 2019 to 2022 The wording of the research issue is how the calculation results of Gross Profit Margin, Net Profit Margin, Return on Assets, and Return on Equity at PT. Timah Tbk. The goal of this research was to identify the growth of PT. Timah Tbk in terms of profitability ratios from 2019 to 2022 by analyzing the results of calculating the Gross Profit Margin, the Net Profit Margin, the Return on Assets, and the Return on Equity at PT. Timah Tbk. This research was conducted with the intention of finding out the outcomes of these calculations. This study makes use of quantitative descriptive data as its primary source of information. This study makes use of secondary data, which includes information collected directly from the primary source (business) that serves as the research object, information obtained from the official website of the firm, and information obtained from the Indonesia Stock Exchange. The information is presented in the form of financial ratios that are taken from the financial reports that are issued at the conclusion of each period of the company's financial statements for PT. Timah Tbk, beginning with the 2019 period and continuing through the 2022 period. According to the findings of this research, the calculation of the profitability ratios of PT Timah Tbk, which is reviewed using Gross Profit Margin, Net Profit Margin, Return on Investment, and Return on Equity, experiences ups and downs (fluctuations). This indicates that the company's ability to gain profits from asset management, equity, and company revenues have decreased and increased, respectively. In terms of profitability ratios, PT. Timah Tbk has seen both growth and decline with each passing year. Therefore, the management at PT. Timah Tbk has relied on profitability ratio analysis as the foundation for their assessment of the company's overall financial performance.